The Effect of Taxpayer Compliance, Tax Collection and Self Assessment System on Tax Revenue - Yuhanis Ladewi; Nunung Nurhayati; Kurnia Krisna Hari; Redi Agustian (Kajian Akuntansi, 2022)
This study aims to determine and analyze taxpayer compliance, tax collection, and the self-assessment system of individual tax receipts in the city of Palembang. The type of research used is descriptive and associative. Sampling used a random method, the sample used was 100 respondents. The data used is primary data by distributing questionnaires to respondents. The analysis used is descriptive statistical analysis and inferential statistical analysis (assumption test and classical multiple linear regression, and hypothesis testing). The results showed that taxpayer compliance has an effect on tax revenue (t count 4.759 > t table 1.660). Tax Collection on Tax Revenue (t count 5,262 > t table 1,660). Self Assessment System has an effect on Tax Revenue (t count 8.394 > t table 1.660) and significant average 0.000 > 0.05 Keywords: Taxpayer Compliance, Tax Collection, System and Taxe revenue